ANALISIS FAKTOR YANG MEMPENGARUHI RATING SUKUK DITINJAU DARI FAKTOR AKUNTANSI DAN NON-AKUNTANSI (STUDI PADA PERUSAHAAN PENERBIT SUKUK YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA) - Fariza Hasanah; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
This study discusses the factors that affect the sukuk rating given by PT PEFINDO in terms of accounting and non-accounting factors for sukuk whose emite is registered with ISSI. PT Pemeringkat Efek Indonesia is a rating agency in Indonesia that has been recognized by OJK. Accounting factors can be seen from the current ratio, debt to equity ratio, total asset turn over, company size; While non- accounting factors can be seen from the maturity or age of sukuk. The purpose of this study is to see what are the factors that affect the sukuk rating given by OJK so that it can be taken into consideration for parties who are related or need this information. This type of research is quantitative with a descriptive quantitative approach. The method used is multiple linear regression. Research data is secondary data obtained through the internet and other sources. The results of the study based on the t test showed that (1) the current ratio variable did not have a significant effect on sukuk rating, (2) the debt to equity ratio variable had a significant effect on sukuk rating, (3) the total asset turn over variable had a significant effect on sukuk rating, (4) the company size variable did not have a significant effect on sukuk rating, (5) sukuk age variable had a significant effect on sukuk rating. And based on test F, the results showed a stimultan influence on the variables of current ratio, debt to equity ratio, total asset turnover, company size, sukuk age, on sukuk rating.